Customer Satisfaction... New Accounting Revolution (Journal of Accounting and Financial Studies ( JAFS ), 2014)
During the ongoing economic revolutions of the economic There is a new economic revolution is emboded by upseting the balances of prevailing classic ideas and refusing axioms considered postulates which were not touched including, for example, the theory of ( supply and demand) espoused by (Adam Smith and Marshall and others ) that assumes the existence of a strong relationship between the supply of goods and services and the demand for them, in the light of successive economic developments, considerable technological progress and the information revolution of the complex telecommunication network led to a serious shift of this theory and the emergence of a new theory called (market economies) turned the traditional scales of production, supply and marketing and the associated developments in accounting science that is one of the branches of the economics. The researcher focuses on the role of cost accounting and its recent developments by introducing new concepts instead of the concepts used previously that included many of the failures where displays the following recent approaches which serve products in terms of cost and quality to meet the requirements of the customer ( customer satisfaction )such as:Firstly: - market competition and consumer taste changesSecondly: - The principle of pull-out rather than the principle of push in the production processThirdly: - appropriate for use instead of conformance with specificationsFourthly: - The concept of customer satisfaction and its effects on:1 - cost2 - QualityFifthly: - (demand and supply) instead of ( supply and demand)The research will address the theoretical side and the applied aspects then the most important conclusions and recommendations within the financial and accounting aspect / accounting and sustainable development.